Mineral exchange within restorative materials following incomplete carious lesion removal using 3D non-destructive XMT subtraction methodology. (August 2020) - Zain, Syed; Davis, Graham R.; Hill, Robert; Anderson, Paul; Baysan, Aylin
Abstract: Objectives: The objective of this study was to quantify the changes in mineral and selected element concentrations within residual carious dentine and restorative materials following incomplete carious lesion removal (ICLR) using different cavity liners, with non-destructive subtraction 3D-X-ray Microtomography (XMT, QMUL, London, UK). Materials and methods: A total of 126 extracted teeth with deep dental caries were assessed using International Caries Risk and Assessment (ICDAS). Eight teeth were subsequently selected after radiographic evaluation. Each lesion was removed, leaving a thin layer of leathery dentine at the deepest part of cavity. Different cavity lining materials were placed; Mineral Trioxide Aggregate (MTA), calcium hydroxide, (Ca(OH)2 ), resin-based material (RBM). For each, the restorative material was an encapsulated glass ionomer (GIC) and the control group had a GIC restoration alone. Each tooth was immediately placed in Simulated Body Fluid (SBF). All samples were then imaged using XMT at baseline, and three weeks after treament. The XMT images were then subtracted to show the mineral concentration changes three weeks after treatment. Results: There were significant increases in mineral concentrations within the residual demineralised dentine in individual teeth treated with Ca(OH)2, MTA, RBM, and GIC following immersion in SBF for three weeks. GIC group without any liners showed the greatest increase in mineral concentration, followed by MTA and Ca(OH)2 . Conclusion: Mineral changes in demineralised dentine and within restorative materials are quantifiable using non-destructive 3D-XMT subtraction methodology. This laboratory study suggested that calcium, phosphate and strontium ion-exchange occurs with GIC, MTA and Ca(OH)2 in deep dentinal lesions following ICLR. Clinical relevance: In clinical practice, incomplete carious lesion removal could be performed to avoid the dental pulp exposure. 3D non-destructive XMT subtraction methodology in a laboratory setting is advantageous to provide evidence for different restorative materials on deep carious lesions prior to clinical investigations.